PEMBERIAN EDUKASI PHBS DAN SCREENING SUHU TUBUH UNTUK PENCEGAHAN COVID 19 DI KABUPATEN PEKALONGAN - Helmi Fatinabila (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2022)
Coronavirus is a group of viruses that can cause disease in animals or humans. Several types of coronavirus are known to cause respiratory tract infections in humans ranging from cold coughs to more serious ones such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). The newly discovered coronavirus causes the disease COVID-19. One way to reduce the risk of being infected or spreading COVID-19 can be done by means of PHBS (Clean and Healthy Lifestyle). Wash your hands often with clean running water and soap, or an alcohol-based hand rub. Maintain a distance of at least 1 meter from people who are coughing or sneezing, when they cough or sneeze, people emit a splash from their nose or mouth and this splash can carry the virus. If you are too close to inhale the splash, you will catch the COVID-19 virus. Avoid touching the eyes, nose and mouth, when the hands touch various surfaces, the virus can be stuck on the hands. Contaminated hands can carry the virus to the eyes, nose or mouth, which are the entry points for the virus to the body.